Biomass models to estimate carbon stocks for hardwood tree species (Forest Systems; Vol 21, No 1 (2012), 2012)
To estimate forest carbon pools from forest inventories it is necessary to have biomass models or biomass expansion factors. In this study, tree biomass models were developed for the main hardwood forest species in Spain: Alnus glutinosa , Castanea sativa , Ceratonia siliqua , Eucalyptus globulus , Fagus sylvatica , Fraxinus angustifolia , Olea europaea var. sylvestris , Populus x euramericana , Quercus canariensis , Quercus faginea , Quercus ilex , Quercus pyrenaica and Quercus suber . Different tree biomass components were considered: stem with bark, branches of different sizes, above and belowground biomass. For each species, a system of equations was fitted using seemingly unrelated regression, fulfilling the additivity property between biomass components. Diameter and total height were explored as independent variables. All models included tree diameter whereas for the majority of species, total height was only considered in the stem biomass models and in some of the branch models. The comparison of the new biomass models with previous models fitted separately for each tree component indicated an improvement in the accuracy of the models. A mean reduction of 20% in the root mean square error and a mean increase in the model efficiency of 7% in comparison with recently published models. So, the fitted models allow estimating more accurately the biomass stock in hardwood species from the Spanish National Forest Inventory data.